Cohort comparisons: emotional well-being among adolescents and older adults - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Ibrahim, Rahimah (Dove Medical Press, 2014)
Background: There are several negative stereotypes about older adults that have negatively influenced people's attitude about aging. The present study compared emotional well-being between older adults and adolescents. Methods: Data for this study came from 1,403 community-dwelling elderly persons and 1,190 secondary school students and were obtained from two national cross-sectional surveys. Emotional well-being was measured using the World Health Organization-Five Well-Being Index. Data analysis was conducted using a multivariate analysis of covariance with SPSS software version 20 (IBM Corporation, Armonk, NY, USA). Results: Elderly people significantly scored higher levels of emotional well-being (mean, 62.3; standard deviation, 22.55) than younger people (mean, 57.9; standard deviation, 18.46; t, 5.32; P≤0.001). The findings from the multivariate analysis of covariance revealed a significant difference between older adults and younger people in emotional well-being [F(3, 2587)=120.21; P≤0.001; η2=0.122] after controlling for sex. Conclusion: Contrary to negative stereotypes about aging, our findings show a higher level of emotional well-being among older adults compared with younger people.